AAC technologies with visual scene displays and "just in time" programming and symbolic communication turns expressed by students with severe disability. Issue 3 (3rd July 2019) - Drager, Kathryn D. R.; Light, Janice; Currall, Jessica; Muttiah, Nimisha; Smith, Vanessa; Kreis, Danielle; Nilam-Hall, Alyssa; Parratt, Daniel; Schuessler, Kaitlin; Shermetta, Kaitlin; Wiscount, Jill
ABSTRACT: Background: The current study investigated the impact of an intervention that included aided augmentative and alternative communication (AAC) technologies on the frequency of symbolic communication turns of school-age children, adolescents, and young adults with severe disability. Method: Nine students ages 8–20 were engaged in interactive activities using an aided AAC system with visual scene displays (VSDs; concepts embedded within a photograph of a naturally occurring event), and "just-in-time" (JIT) programming (the capability to add new contexts "on the fly"). Effectiveness was evaluated using a single subject multiple probe across participants design. Results: All participants demonstrated increases in symbolic communication turns upon introduction of the AAC technologies with VSDs using JIT technology. Conclusions: AAC with VSDs and JIT programming may be effective in increasing symbolic communication for students with severe developmental disability. The fast and easy creation of VSDs and hotspots to provide communication may be a valuable tool for interventionists.